Incidence and predictors of lost to follow-up among women under Option B+ PMTCT program in western Ethiopia: a retrospective follow-up study - Tolossa, Tadesse (BMC Res Notes, 2020)
OBJECTIVE: Although Ethiopia has been implementing Option B+ program, LTFU of women from the Option B+ program is one of the challenges that minimizes its implementation. Thus, this study assessed the incidence and predictors of LTFU among women under Option B+ PMTCT program in western Ethiopia. An institution-based retrospective follow-up study was conducted. A cox proportional hazards regression model was fitted to identify predictors of LTFU. A Hazard ratios with 95% confidence CI was computed and all predictors that were associated with the outcome variable at p-value ≤ 0.05 in the multivariable cox proportional hazards were declared as a significance predictor of the outcome. RESULTS: A total of 330 women were followed for a mean follow up time of 16.9 (± 7.6) months. An overall incidence rate of LTFU was 9/1000 person-months. Women’s educational status, residence, HIV-disclosure status, the status of women at enrollment, previous history of HIV and ART adherence were significant predictors of LTFU. The incidence of LTFU from Option B+ PMTCT is lower as compared to evidence from sub-Saharan African and strengthening linkage and referral system between clinics as well as establishing appropriates tracing mechanisms would retain pregnant women in the program.